Different Behavior of Commercial Nickel and Ruthenium Catalysts on Biogas Upgrading - Gimeno Izquierdo, Chuan; Mercader Plou, Victor Daniel; Durán Sánchez, Paúl; Peña Llorente, José Ángel; Herguido Huerta, Francisco Javier (Jornada de Jóvenes Investigadores del I3A, 2025)
This study investigates the behavior of five commercial catalysts based on Ni or Ru oxides as active phases for CO₂ methanation at atmospheric pressure. The research evaluates the influence of both temperature and the partial pressure of the reactants on the performance of the different catalysts studied.